Penghasilan dan pencirian eksopolisakarida daripada Bacillus lichenformis S20A - Mat Isa, Anida (2004)
In suitable surrounding environment, living microorganisms are able to produce side products. Exopolysaccharide, EPS is one of the side products in bacterial growth activities. Many EPS from bacteria has been studied and used widely. Among those are xanthan, alginate and curdlan. This study is purposely to culture bacteria isolated from local oil field in a medium that can produce biopolymer prior to characterization process. When cultured in sucrose medium at 45 degree celcius, shaker speed at 200 rpm for 22 hours Bacillus licheniformis S20A is able to produce optimum EPS. Different carbon and nitrogen sources used in bacterial growth study were found to produce EPS with same functional group. Bacterial was grown following the typical growth curve consist of lag phase, log phase, stationary phase and death phase. Characterization carried out to identifer the functional group and monomer that build up the EPS. Structure and EPS type were analyzed using FTIR and 'H NMR. Thermal analysis was carried out using DSC and TGA technique. Solubility test has been done in organic and inorganic solvents. Molecular weight and distribution was measured using viscometry and GPC method. EPS rheology upon concentration and temperature was also studied. Result in FTIR spectrum indicate the functional group of.EPS S20A is C=OH. Only one anomeric refers to a-D mannose was detected in 'H NMR spectrum. EPS S20A is a polymannose with molecular weight viscosity-average around 1.7 x lo5 to 1.54 x lo6 glmol. The molecular weight viscosity-average was found increased when Bacillus lichenformis S20A is cultured more than 22 hours, but the amount of EPS S20A produced is decreased . GPC method indicate EPS S2bA have a polydispersity index of 1.06. EPS S20A is a hygroscopic polymer tend to melt at Tmom,t 124SÂ°C and degraded at 200.0Â°C. EPS S20A shows pseudoplastik behavior when used in concentration higher than 4%.